2015
DOI: 10.1002/jssc.201500994
|View full text |Cite
|
Sign up to set email alerts
|

Application of linear pH gradients for the modeling of ion exchange chromatography: Separation of monoclonal antibody monomer from aggregates

Abstract: The mobile phase pH is a key parameter of every ion exchange chromatography process. However, mechanistic insights into the pH influence on the ion exchange chromatography equilibrium are rare. This work describes a mechanistic model capturing salt and pH influence in ion exchange chromatography. The pH dependence of the characteristic protein charge and the equilibrium constant is introduced to the steric mass action model based on a protein net charge model considering the number of amino acids interacting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“… All parameters were given by manufacturer. Other parameters were determined according to Kluters et al…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… All parameters were given by manufacturer. Other parameters were determined according to Kluters et al…”
Section: Methodsmentioning
confidence: 99%
“…In the linear range of the isotherm (i.e. at low protein loading), the distribution coefficient Anormali can be calculated as the ratio between adsorbed protein concentration in the stationary phase qE,i and protein concentration in the mobile phase cnormali, i.e., Anormali=qE,i/cnormali . The characteristic binding charge of the protein ν is a function of pH which is defined by Schmidt et al based on the protein net charge model as: ν=iNi1+10pKaipH+iN+i1+10pHpKai where the number of acidic amino acids is Ni ( NCarboxyl, NTyr) and the number of each basic amino acid is N+i ( NArg, NLys, NHis, NNTerm) involved in protein‐ligand binding.…”
Section: Theoretical Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such buffer systems have recently been described by a group specializing in the modeling of pH gradients for IEX. 38,39 An additional consideration for preparative scale purifications is the stability of the protein at the starting pH of the separation, since the protein mixture is usually being loaded onto the column in a buffer of the same pH. Although we did not encounter any stability issues at the high end of the pH range (the loading pH for AEX), we found that, especially for BsAbs made up of IgG4 parents, a starting pH of 4.0 led to significant amounts of aggregation (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Fitting the number of each charged residue in this set to chromatographic data provided a functional description of pH and salt gradient elution. Kluters et al extended the work of Schmidt and coworkers to overloaded conditions using the SMA model but did not validate high protein load conditions with a combined pH‐salt gradient. In yet another approach, Vetter et al fitted the SMA model to isotherm data describing mAb binding to a CEX resin as a function of protein and salt concentration and then correlated the dependence of the protein binding charge on pH using a linear empirical relationship.…”
Section: Introductionmentioning
confidence: 99%